An investigation of [5, 3] error correcting codes over GF(5). Issue 3 (3rd April 2018) - Ghose, Apu Kumar; Dey, Partha Pratim
Abstract: In papers [1, 2], we were able to classify all 1-error correcting [5, 3] and [5, 2] codes over GF (4). In this paper, we investigate the existence and equivalence of [5, 3] error correcting codes over GF (5). It appears that these codes are all mutually equivalent. We also calculate their weight distribution as well as the weight distribution of their orthogonal codes.